The in Vitro Antiplasmodial and Antiproliferative Activity of New Ferrocene‐Based α‐Aminocresols Targeting Hemozoin Inhibition and DNA Interaction. (27th May 2020) - Mbaba, Mziyanda; Dingle, Laura M. K.; Swart, Tarryn; Cash, Devon; Laming, Dustin; de la Mare, Jo‐Anne; Taylor, Dale; Hoppe, Heinrich C.; Biot, Christophe; Edkins, Adrienne L.; Khanye, Setshaba D.
Abstract: The conjugation of organometallic complexes to known bioactive organic frameworks is a proven strategy revered for devising new drug molecules with novel modes of action. This approach holds great promise for the generation of potent drug leads in the quest for therapeutic chemotypes with the potential to overcome the development of clinical resistance. Herein, we present the in vitro antiplasmodial and antiproliferative investigation of ferrocenyl α‐aminocresol conjugates assembled by amalgamation of the organometallic ferrocene unit and an α‐aminocresol scaffold possessing antimalarial activity. The compounds pursued in the study exhibited higher toxicity towards the chemosensitive (3D7) and ‐resistant (Dd2) strains of the Plasmodium falciparum parasite than to the human HCC70 triple‐negative breast cancer cell line. Indication of cross‐resistance was absent for the compounds evaluated against the multi‐resistant Dd2 strain. Structure‐activity analysis revealed that the phenolic hydroxy group and rotatable σ bond between the α‐carbon and NH group of the α‐amino‐ o ‐cresol skeleton are crucial for the biological activity of the compounds. Spectrophotometric techniques and in silico docking simulations performed on selected derivatives suggest that the compounds show a dual mode of action involving hemozoin inhibition and DNA interaction via minor‐groove binding. Lastly, compound 9 a, identified as a possible lead, exhibited preferential binding for the plasmodial DNA isolated from 3D7 P. falciparum trophozoites over the mammalian calf thymus DNA, thereby substantiating the enhanced antiplasmodial activity of the compounds. The presented research demonstrates the strategy of incorporating organometallic complexes into known biologically active organic scaffolds as a viable avenue to fashion novel multimodal compounds with potential to counter the development drug resistance. Abstract : Multitarget attack : Compounds incorporating ferrocene in a aminocresol scaffold showed antiplasmodial and anticancer activity. SAR studies revealed that an OH group and rotatable C–NH bond are vital for biological activity, with spectrophotometric techniques and docking simulations suggesting a dual mode of action involving hemozoin inhibition and DNA interaction. Targeting multiple pathways could delay the development of clinical resistance.